2019
DOI: 10.1136/rmdopen-2019-000955
|View full text |Cite
|
Sign up to set email alerts
|

Time in remission and low disease activity state (LDAS) are associated with a better quality of life in patients with systemic lupus erythematosus: results from LUMINA (LXXIX), a multiethnic, multicentre US cohort

Abstract: AimsTo determine whether the proportion of time systemic lupus erythematosus patients achieve remission/low disease activity state (LDAS) is associated with a better quality of life (QoL).Patients and methodsPatients from a well-established multiethnic, multicentre US cohort were included: remission: Systemic Lupus Activity Measure (SLAM) score=0, prednisone≤5 mg/day and no immunosuppressants); LDAS not in remission, SLAM score≤3, prednisone≤7.5 mg/day, no immunosuppressants; the combined proportion of time pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…We here confirm that LLDAS is associated with better HRQoL using an SLE-specific instrument. Two very recent studies in the USA and Latin America have demonstrated longitudinal associations between LLDAS and improved HRQoL assessed using the generic SF36 as well as the SLE-specific LupusQoL survey [46,47]. This observed association between LLDAS and improved HRQoL is important given LLDAS is a composite measure of both disease activity and treatment burden and an attainable target for SLE patient treatment.…”
Section: Discussionmentioning
confidence: 94%
“…We here confirm that LLDAS is associated with better HRQoL using an SLE-specific instrument. Two very recent studies in the USA and Latin America have demonstrated longitudinal associations between LLDAS and improved HRQoL assessed using the generic SF36 as well as the SLE-specific LupusQoL survey [46,47]. This observed association between LLDAS and improved HRQoL is important given LLDAS is a composite measure of both disease activity and treatment burden and an attainable target for SLE patient treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The findings which highlight that disease activity fully mediated the effects of HCQ on PROs is plausible as higher disease activity often results in impairment of physical, emotional and social health, thereby impairing the QOL and adversely impacting patient’s daily life. 29,30 Evidence affirms that HCQ results in reduced disease activity, 811 and HCQ can thereby result in improvements in QOL and decrease the adverse impact of SLE on patients daily lives. These findings can help enhance patient’s acceptability of HCQ, which despite its numerous well-established beneficial effects, remains a major issue in roughly half of the SLE patients due to non-adherence.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, enrolled patients had a significantly shorter disease duration compared to our study (1.4 vs 14 years). Finally, the authors used different definitions of remission and low disease activity for their study according to which a stable immunosuppressive treatment was not included in the conditions of remission or low disease activity [30]. The impact of remission duration on patient's quality of life is well exemplified by Mok et al whose study, conducted on a large cohort of SLE Chinese patients with a mean disease duration of 12.6 ± 8.1 years, demonstrated that a durable remission could be achieved in almost a quarter of patients; however, only patients with remission of ≥ 5 years presented a significantly better QoL assessed using both SF-36 and Lupus-PRO [31].…”
Section: Discussionmentioning
confidence: 99%